KEANEKARAGAMAN ASPERGILLUS PADA BERBAGAI TRADISIONAL SIMPLISIA JAMU - Rukmi, Isworo (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT---The  presence  of Aspergillas sp. in the simplisia  commonly consumed by Javanese people as a  traditional  medicine has been done. The  eight  simplisia  examined were:  kunyit  rhizome (Cucurma domesfica Val.), temuireng  rhizome (Cucurma aeroginosae), daun sambiloto (Andrographis paniculata), temulawak rhizome (Cucurma xanthorhizu), and mahkota  dewa (Phaleria macrocarpa). Sixteen Aspergillus  species were found from the samples, came from the niger,  flavus, versicolor, wentii, fumigatus, ochraceus dan ornatus  group.  Isolates found  in  this  study  were A. parositicus, A. flavas,  A. oryzae, A. tamarin, A. clavato-flavus, A. flavofurcatis, A. tubingiensis, A. awamori, A. ochraceus, A. sulphureus, A. melleus, A. ornatus, A. brunneo-uniseriatus, A. versicolor, A.  wentii, and A. fumigatus,  the first six are the member of flavus group  that  found  in  all  simplisia samples. Nine species of the isolatesknown as mycotoxin producers.Keywords : Aspergillus, simplisia, mikotoksin